Furniture design - Smardzewski, Jerzy; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
Maximizing reader insights into the principles of designing furniture as wooden structures, this book discusses issues related to the history of furniture structures, their classification and characteristics, ergonomic approaches to anthropometric requirements and safety of use. It presents key methods and highlights common errors in designing the characteristics of the materials, components, joints and structures, as well as looking at the challenges regarding developing associated design documentation. Including analysis of how designers may go about calculating the stiffness and endurance of parts, joints and whole structures, the book analyzes questions regarding the loss of furniture stability and the resulting threats to health of the user, putting forward a concept of furniture design as an engineering processes. Creating an attractive, functional, ergonomic and safe piece of furniture is not only the fruit of the work of individual architects and artists, but requires an effort of many people working in interdisciplinary teams, this book is designed to add important knowledge to the literature for engineer approaches in furniture design.
The History of Furniture Construction -- Classification and Characteristics of Furniture -- Ergonomics of Furniture -- Introduction to Engineering Design of Furniture -- Technical Documentation -- Stiffness and Strength Analysis of Skeletal Furniture -- Stiffness and Strength Analysis of Case Furniture -- Stiffness and Strength Analysis of Upholstered Furniture.
Electronic reproduction.
Keywords: Furniture design; Electronic books